Effect of cassava (Manihot esculenta cranzt), rice (Oryza sativa L.), and potato (Solanum tuberosum) water extract to decrease pH phase fermentation of Streptococcus mutans ATCC 25175 - Imelda, Reza Afri; Mariam, Marry Siti; Satari, Mieke Hemiawati (Padjadjaran Journal of Dentistry, 2019)
Introduction: Dental caries is the localised damage of the hard tooth tissue caused by acid production results of carbohydrate fermentation by acid-producing bacteria. Streptococcus mutans are one of the aetiological bacteria which fermented carbohydrate causes a decrease in the oral pH. Carbohydrate is generally consumed, included cassava, rice, and potato. The purpose of this study was to determine the mechanism of the water extract of rice, cassava, and potato in decreasing the pH of Streptococcus mutans culture to know their potential in causing caries and also determined decreasing differences between three water extracts. Methods: The experimental method was used in cultured Streptococcus mutans ATCC 25175 and tested against the treated rice, cassava, and potato water extract. Cultured bacteria were incubated for 48 hours in facultative anaerobes then measured the pH with a digital pH meter. The measurement result was statistically tested with the paired t-test and ANOVA. Results: The paired t-test (α = 0.05) showed that the p-value of rice, cassava, and potato water extract were 0.001, 0.001, and 0.018 respectively. ANOVA test with an α value of 0.05 showed the p-value of 0.000. Conclusion: There was a decrease in pH of cultured Streptococcus mutans after administration of the water extract of cassava, rice, and potato, and there was a difference between the pH decrease of the Streptococcus mutans between administration of water extract of rice, cassava, and potato. Keywords: Streptococcus mutans, Manihot esculentacrantz, Oryza sativa L., Solanum tuberosum, pH phase fermentation